Maximizing the relevance and reproducibility of A549 cell culture using FBS-free media. (September 2022) - Chary, Aline; Groff, Katherine; Stucki, Andreas O.; Contal, Servane; Stoffels, Charlotte; Cambier, Sébastien; Sharma, Monita; Gutleb, Arno C.; Clippinger, Amy J.
Abstract: Scientists are using in vitro methods to answer important research questions and implementing strategies to maximize the reliability and human relevance of these methods. One strategy is to replace the use of fetal bovine serum (FBS)—an undefined and variable mixture of biomolecules—in cell culture media with chemically defined or xeno-free medium. In this study, A549 cells, a human lung alveolar-like cell line commonly used in respiratory research, were transitioned from a culture medium containing FBS to media without FBS. A successful transition was determined based on analysis of cell morphology and functionality. Following transition to commercially available CnT-Prime Airway (CELLnTEC) or X-VIVO™ 10 (Lonza) medium, the cells were characterized by microscopic evaluation and calculation of doubling time. Their genotype, morphology, and functionality were assessed by monitoring the expression of gene markers for lung cell types, surfactant production, cytokine release, the presence of multilamellar bodies, and cell viability following sodium dodecyl sulphate exposure. Our results showed that A549 cells successfully transitioned to FBS-free media under submerged and air-liquid-interface conditions. Cells grown in X-VIVO™ 10 medium mimicked cellular characteristics of FBS-supplemented media while those grown in CnT-Prime Airway medium demonstrated characteristics possibly more reflective of normal human alveolar epithelial cells. Highlights: A549 cells transitioned from FBS-supplemented media to commercial serum-free media. A gradual weaning process was successful under submerged and ALI conditions. Genotype, morphology, and functionality in different media formulations were assessed. Cells grown in X-VIVO™ 10 medium mimicked characteristics of FBS-supplemented media. Cells grown in CnT-Prime Airway more closely resembled an in vivo alveolar phenotype.